Investigation on the hesitancy of COVID-19 vaccination among liver transplant recipients: A cross-sectional study in China - Pan, Yixiao; Gong, Shiming; Zhu, Xinye; Xue, Chuqing; Jing, Yilei; Sun, Yinghua; Qian, Yongbing; Zhang, Jianjun; Xia, Qiang (Frontiers in Public Health, 2022)
Objectives The hospitalization and mortality rate from COVID-19 appears to be higher in liver transplant recipients when compared with general populations. Vaccination is an effective strategy to reduce the risk during the COVID-19 pandemic. We aimed to evaluate COVID-19 vaccine hesitancy in liver transplant recipients. Methods In April 2022, we conducted an online-based survey through WeChat platform to investigate the vaccination hesitancy among liver transplant recipients followed at Shanghai Renji Hospital and further explore possible influencing factors. Survey items included multiple choice, Likert-type rating scale and open-ended answers. Participants were classified as no hesitancy group and hesitancy group. Using univariate analysis, ROC curve analysis and multiple logistic regression to evaluate associations between baseline characteristics and COVID-19 vaccine hesitancy. Results 449 liver transplant recipients participated in the survey with 299 (66.6%) of them being categorized as vaccine hesitancy. In no hesitancy group, 73 (48.7%) recipients had completed vaccination, while 77 (51.3%) were not yet but intended to be vaccinated. In contrast, 195 (65.2%) recipients in hesitancy group were hesitant to get vaccinated, while the remaining 104 (34.8%) refused. The most common side effect was injection arm pain (n = 9, 12.3%). The common reasons for vaccine willingness was trusted in the effectiveness of the vaccine and fear of contracting COVID-19. The most common reason for vaccination hesitancy is fear of side effects, and the most effective improvement was the support from the attending physician. Factors associated with vaccine hesitancy include female sex, influenza vaccination status, awareness of the importance and safety of vaccine, attitudes of doctors and others toward vaccine, medical worker source information of vaccine, relative/friend with medical background, total score of VHS (Vaccine Hesitancy Scale), accessibility of vaccine. Conclusion For liver transplant recipients, COVID-19 vaccine is an important preventive measure. Identifying the factors influencing COVID-19 vaccine hesitancy is therefore critical to developing a promotion plan. Our study shows that more comprehensive vaccine knowledge popularization and relevant medical workers' training can effectively improve the acceptance of COVID-19 vaccine in this population.